Drug-induced lupus - Hess, Evelyn (Henry Stewart Talks, 2007)
The occurrence of drug and environment-related lupus and lupus-like syndromes, The medications that have been reported in association with autoimmune symptoms and syndromes, The major associations and cause(s) of these commonly noted clinical syndromes